Supported by CGIAR and partners’ research, the South Africa government invests in water resources, irrigation and infrastructure improvements and adopts policies for climate change resilience - CGIAR Research Program on Policies, Institutions, and Markets (2021)
Since 2013, the Government of South Africa, WLE/PIM/IFPRI and research partners have collaborated to assess the role of water infrastructure in adapting to potential climate change impacts. This has led policy makers to prioritize building resilience into infrastructure investments and to implement climate-sensitive development programs. The findings and recommendations of this research have been integrated into major policy and investment plans, including Operation Vulindlela, highlighted in the President’s 2022 State of the Nation Address.